Serum IL-17 and postmenopausal osteoporosis - AL-Tai, Tharwa H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Osteoporosis is a bone condition that makes bones thininer and more fragile because of reduced bone density and it puts people at risk of fractures, especially of the hip, spinal vertebrae and wrist.Objective: This study will highlighted the role of IL-17 in postmenopausal osteoporosis.Patients and methods: This study applied on 84 includes subjects (42 postmenopausal osteoporosis patient and 42 of healthy control group), conducted from December 2014 to March 2015 to measure the IL-17 serum level by using ELISA kit.Results: In osteoporotic postmenopausal women the mean of serum IL-17 was (0.49pg/ml) and it is significantly higher than that of healthy group (0.09pg/ml).Conclusion: Serum IL-17 was significantly elevated in osteoporotic postmenopausal women when compared to healthy postmenopausal women.